Pengaturan Tata Letak Produk Fashion dengan FP-Growth untuk Peningkatan Penjualan UMKM - Widyasari; Syafiqoh, Ummi; Rahmadania, Nova Tari; Hartono, Lies (STMIK PPKIA Tarakanita Rahmawati, 2025)
The application of data mining techniques in the business sector contributes significantly to strategic decision-making. This study implements the FP-Growth algorithm to analyze consumer purchasing patterns at Zaynthary Store, a fashion retail shop located in Tarakan City. A total of 161 sales transaction records were collected and processed to identify frequent itemsets and association rules that represent relationships between products. The findings reveal that certain item combinations are frequently purchased together, such as Blouse → Jeans with a confidence value of 55%, suggesting that these items should be placed near each other in the store display layout. FP-Growth has proven effective in exploring customer purchase patterns and providing layout recommendations that can support increased sales. These results can serve as a strategic reference for designing data-driven store layouts in the fashion retail industry.